Factors associated with number of duodenal samples obtained in suspected celiac disease - Shamban, Leonid; Sorser, Serge; Naydin, Stan; Lebwohl, Benjamin; Shukr, Mousa; Wiemann, Charlotte; Yevsyukov, Daniel; Piper, Michael H.; Warren, Bradley; Green, Peter H. R. (Endoscopy International Open, 2017)
Background and study aims Many people with celiac disease are undiagnosed and there is evidence that insufficient duodenal samples may contribute to underdiagnosis. The aims of this study were to investigate whether more samples leads to a greater likelihood of a diagnosis of celiac disease and to elucidate factors that influence the number of samples collected. Patients and methods We identified patients from two community hospitals who were undergoing duodenal biopsy for indications (as identified by International Classification of Diseases code) compatible with possible celiac disease. Three cohorts were evaluated: no celiac disease (NCD, normal villi), celiac disease (villous atrophy, Marsh score 3), and possible celiac disease (PCD, Marsh score < 3). Endoscopic features, indication, setting, trainee presence, and patient demographic details were evaluated for their role in sample collection. Results 5997 patients met the inclusion criteria. Patients with a final diagnosis of celiac disease had a median of 4 specimens collected. The percentage of patients diagnosed with celiac disease with one sample was 0.3 % compared with 12.8 % of those with six samples (P = 0.001). Patient factors that positively correlated with the number of samples collected were endoscopic features, demographic details, and indication (P = 0.001). Endoscopist factors that positively correlated with the number of samples collected were absence of a trainee, pediatric gastroenterologist, and outpatient setting (P < 0.001). Conclusions Histological diagnosis of celiac disease significantly increased with six samples. Multiple factors influenced whether adequate biopsies were taken. Adherence to guidelines may increase the diagnosis rate of celiac disease.